Creating Livelihoods Enhancing Medicinal and Aromatic Plants based Biodiversity-Rich Production Systems: Preliminary Lessons from South Asia - M. Karki, Brajesh Tiwari, A. Badoni, N. Bhattarai
The literature defines livelihoods as `the processes comprising the capabilities, assets and activities that provide a means for living' to the human beings. Livelihoods are best examined through Sustainable Livelihoods Framework (SLF), which is based on the premise that livelihood is not about resource productivity but it is about people and their lives. Livelihoods are sustainable when they are: a) resilient to shocks and stresses, b) independent of external support, c) maintain the productivity (and diversity) of natural stocks; and d) do not adversely affect the livelihoods of others. In other words, SLF: a) builds on the strengths of people, their resources and knowledge systems, b) strengthens local institutional capacity, c) attempts to remove conditions causing poverty rather than poverty itself, and d) gives priority to improving policies, processes and institutions in developing and implementing programs.